Неполнота знаний как причина суеверий в науке и образовании - Терещенко, В. В. (ХНУРЭ, 2012)
Since the establishment of science as a socially important institution, she always had to compete with the religious dogmas and precepts of the universe. Interestingly, the lack of knowledge in science leads to the perception of the blind material and superstitious dogmatic acquisition of knowledge. Need to improve the quality and perception of the responsibility of the material, the realization of a pair